Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper for Chile assesses the impact of the global financial crisis on Chilean banks. It provides a framework for analyzing government measures aimed at reducing systemic risk. The analysis suggests that Chilean banks are resilient to global and regional shocks. However, even in the absence of direct exposures with other countries in the region, there may be risk spillovers from other banks in the region and in advanced economies. The paper also presents options for further strengthening Chile's fiscal framework.